ANALISIS PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN SEPEDA MOTOR MATIC PADA DEALER JAYA TERANG 2 DI KABUPATEN SITUBONDO DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - Handoni, Tirta; Soeliha, Siti; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The aim of the study was to determine the Analysis of the Influence of Price and Product Quality on Consumer Loyalty of Matic Motorcycles at Jaya Terang 2 Dealers in Situbondo Regency with Purchasing Decisions as Intervening Variables. The sampling technique used in this study was simple random sampling of 92 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that price has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions, price has a negative but significant effect on consumer loyalty, product quality has a positive and significant effect on consumer loyalty. , Purchase decisions have a positive and significant effect on repeat customer loyalty, Price has a positive and significant effect on consumer loyalty through purchasing decisions, Product quality has a positive and significant effect on consumer loyalty through purchasing decisions.